The history of terrorism : from antiquity to ISIS - d; Blin, Arnaud (Oakland, California : University of California Press, 2016)
"This authoritative work provides an essential perspective on terrorism by offering a rare opportunity for analysis and reflection at a time of ongoing violence, chilling threats, and renewed reprisals. In it, some of the best international specialists examine terrorism's long and complex history from antiquity to the present day and find that terror, long the weapon of the weak against the strong, is a tactic as old as warfare itself. Beginning with the Zealots of Antiquity, contributors discuss the Assassins of the Middle Ages, the 1789 Terror movement in Europe, Bolshevik terrorism during the Russian Revolution, Stalinism, resistance terrorism during World War II, and Latin American revolutionary movements of the late 1960s. Finally, they consider the emergence of modern transnational terrorism, focusing on the roots of Islamic terrorism, al Qaeda, and the rise of the contemporary suicide martyr. Along the way, they provide a groundbreaking analysis of how terrorism has been perceived throughout history. What becomes powerfully clear is that only through deeper understanding can we fully grasp the present dangers of a phenomenon whose repercussions are far from over. In this updated edition, Chaliand and Blin have included a new chapter on ISIS and analysis of key events as they have unfolded including the 2015 Paris attacks." --
Preface to the 2016 edition -- Preface to the 2007 edition -- 1. Introduction / g 4. Manifestations of terror through the ages / g 6. Anarchist terrorists of the Nineteenth Century / Olivier Hubac-Occhipinto ; 7. Russian terrorism, 1878-1908 / Yves Ternon ; 8. The "Golden Age" of terrorism / g 10. Terrorism in time of war: from World War II to the wars of national liberation / g 12. The roots of Islamic radicalism / Philippe Migaux ; 13. Al Qaeda / Philippe Migaux ; 14. The future of the Islamist movement / Philippe Migaux ; 15. Suicide operations: between war and terrorism / g
Translated from the French.
"With a new preface and final chapter."
Includes preface to the 2007 edition.
First published in English in 2007 under title: The history of terrorism : from antiquity to al Qaeda.
Includes bibliographical references and index.
Keywords: Terrorism -- History